Comparative analysis of acute and chronic painful temporomandibular disorders: Insights into pain, behavioral, and psychosocial features - Adrian Ujin Yap; Jung Hwan Jo; Sunghae Kim; Byeong-min Lee; Ji Woon Park (PLoS ONE, 2025)
Objective The scarcity of literature necessitates further research to differentiate between acute and chronic painful temporomandibular disorders (TMDs). This study compared pain characteristics, oral behaviors, jaw function, and psychosocial distress between TMD patients with acute and chronic pain, examined correlations among variables, and identified factors associated with chronic pain-related TMDs (PT). Methods Anonymized data were gathered from consecutive patients seeking TMD treatment at a university-based oral medicine clinic. Axis I diagnoses were made using the Diagnostic Criteria for TMDs, and patients with PT were categorized into acute (AP) and chronic pain (CP) groups. Axis II assessments were performed, evaluating pain characteristics, oral behaviors, jaw functional limitation, somatic symptoms, depression, and anxiety. Statistical analysis utilized chi-square/non-parametric tests and logistic regression (α =  0.05). Results Among the 488 PT patients, 34.6% experienced AP and 65.4% had CP. Significant differences were observed in pain intensity, interference, disability, jaw overuse behavior, functional limitation, somatic symptom burden, depression, and anxiety. (CP>  AP). Moderate-to-strong correlations were found in both the AP (rs =  0.43–0.83) and CP (rs =  0.46–0.87) groups, although the specific relationships between pain, behavioral, and psychosocial factors differed somewhat. The multivariate regression model revealed that only pain intensity (OR =  1.01) and oral behaviors (OR =  1.06) significantly increased the odds of chronic PT. Conclusion Chronic pain was more prevalent in PT patients and associated with greater severity in pain, behavioral, and psychosocial variables. Pain intensity and oral behaviors were linked to an increased likelihood of chronic pain.